Bimbingan Pra Nikah, Partisipasi Masyarakat, dan Ketahanan Keluarga: Studi Kasus di Kecamatan Grogol Kediri - Muhammad Ainul Yakin; Khoirul Anwar; Syaiful Makhi Ula Arrois (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study aims to analyze community participation in premarital guidance services in Grogol District, Kediri, from the perspective of sociology of law and legal consciousness. This research employs a qualitative field research approach through observation, interviews, and documentation. The analysis uses a socio-legal approach to understand the relationship between legal norms, social culture, religious relations, and community social practices in premarital guidance services. The findings reveal that community participation is not entirely based on substantive legal awareness, but is still influenced by administrative compliance, socio-religious legitimacy, educational background, family environment, and public perceptions of the role of the Office of Religious Affairs (KUA). On the other hand, premarital guidance services have important implications for strengthening legal awareness, improving family communication, and functioning as a preventive instrument to minimize domestic conflict and divorce. This study confirms that the effectiveness of premarital guidance services is determined not only by formal regulations, but also by the social, educational, and cultural approaches developed by KUA within the community.